Effects of Voluntary and Involuntary Real Lab Situations on Personal Carbon Footprints of Private Households. Experiences From Germany - Reusswig, Fritz; Bock, Seraja; Schleer, Christoph; Lass, Wiebke (Frontiers in Sustainability, 2021)
This paper compares the carbon footprint effects of a voluntary real lab with those of the involuntary ‘real lab’ provided by the lockdowns during the recent Corona crisis. In a voluntary real lab situation, 100 private households in Berlin (Germany) have tried to reduce their personal carbon footprints over one year (2018). The households have been equipped with a weekly carbon tracker, calculating their CO2e footprint in the domains housing energy, mobility on ground, air travel, food, other consumption, and public consumption. The households have been informed by various channels and supported by a network of 'green' local enterprises and NGOs. It was also possible for them to make use of in-home energy advisors, identifying easy-to-accomplish saving potential. On average, the households managed to reduce their footprint by 11 %, with individual savings of up to 40%. One of the major problems the households have been experiencing was refraining from air travel, e.g. by substituting it by train l. Others identified road safety as a major problem when switching from cars to bikes. With an annual reduction of 10%, carbon neutrality could be reached in or even before 2050. But political decisions are needed in order to change the collective boundary conditions. In 2020, Germany--as many other countries--has experienced a COVID-19 lockdown with substantial restrictions to all kinds of consumption activities (flying, international travel, consumption activities in the public etc.). This work compares the CO2 reduction effects of these two 'real labs', a voluntary and an imposed one, and ask what the relative quantitative effects are. Following that comparison, it reflect upon the similarities and differences of voluntary and imposed situations, and what there can be learned for the implementation of policies for more sustainable production and consumption patterns. 1 In this paper CO2 is meant as a synonym to CO2 equivalent (CO2e), comprising CO2 and other important greenhouse gases such as methane (CH4) or nitrous oxide (N2O).